Faktor Keberhasilan Smart Mobility menggunakan DeLone McLean dan Model Adopsi E-Government: Faktor Keberhasilan Smart Mobility menggunakan DeLone McLean dan Model Adopsi E-Government - Hernu Haryono; Faris Muslihul Amin; Nurissaidah Ulinnuha (Universitas Muhammadiyah Sorong, 2023)
E-government is an information systems for public services with an easily accessible and efficient system used by the government. This research aims to find out the factors influencing success and adoption using the DeLone McLean model and the E-Government Adoption Model (GAM) in the implementation of the TransportasiKu application of the Surabaya Transportation Agency. This research used a quantitative approach by collecting data through questionnaires using a measurement scale, namely the Likert scale. The sample collection technique for this research was simple random sampling with 100 respondents in total samples. The technique of data analysis in this research used SEM-PLS. The results of this study found that of the eight hypotheses proposed, five were accepted while the other three were rejected. Computer Self-Efficacy and Perceived Trust positively and significantly affect E-government Adoption. Information Quality has a positive and meaningful effect on the Intention to Use. E-government Adoption and Intention to Use positively and significantly affect Net Benefit. Meanwhile, Perceived Awareness of E-government Adoption, System Quality, and Service Quality towards Intention to Use results are not significant.